THE EFFECT OF COMMUNICATION AND JOB PROMOTION ON EMPLOYEE PERFORMANCE OF PT. BANK SYARIAH INDONESIA, TBK KCP LHOKSEUMAWE MERDEKA SIMPANG EMPAT CITY OF LHOKSEUMAWE - Yusnidar; Muhammad Multazam; Ismuhadi; Ayu Anora; Irda Agustina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Human resources must have tangible assets when dealing with business, so employees are encouraged to contribute to the business every day because the business succeeds or fails. Every worker has the opportunity to gradually increase the number of hours they work by being blessed with their personal skills. This study aims to determine how communication and job promotion affect the performance of employees of PT. Bank Syariah Indonesia, Tbk KCP Lhokseumawe Merdeka Simpang Empat Lhokseumawe City. This study uses quantitative information. The results of the study showed that the R^2 value was 0.956, and other variables influenced most of the data. The significant value of t_count of Communication (X1) was 3.717 and the significant value of t_count of Job Promotion (X2) was 5.773 with a ttable value of 1.699 having a positive and significant effect on the performance of employees of PT. Bank Syariah Indonesia, Tbk KCP Lhokseumawe Merdeka Simpang Empat Lhokseumawe City. In this case, communication must be maintained, because communication is a good relationship in increasing trust in carrying out performance. For job promotions, at least the organization must think about the level of comfort in carrying out performance in continuing something deeper in placing the job position.